HUBUNGAN NON-MONOTONIK ANTARA KEPEMILIKAN MANAJERIAL DENGAN DISCRETIONARY ACCRUALS - Kurnia Putri Hidayaningtyas; Agung Juliarto (Diponegoro Journal of Accounting, 2017)
This study aims to examine non-monotonic relation between the value of managerial ownership and percentation of managerial ownership to discretionary accruals. The value of executive share ownership (VESO) is potentially a more  direct driver of incentive alignment and/or entrenchment than the proportion of ownership. This study use percentation of managerial ownership and value of managerial ownership as variables expected to affect discretionary accruals. This study based on research conducted by Khan and Mather (2013).Population of this study are non – financial companies listed in Indonesia Stock Exchange (IDX) 2012,2013, and 2014. The sampling method used is purposive sampling. Total sample of 232 companies is used in analysis. Data are analyzed using ordinary least square (OLS).The results of this study indicate that the value of managerial ownership (VESO) has a non-monotonic relation to discretionary accruals. However, this study does not find a non-monotonic relation between percentation of managerial ownership to discretionary accruals.